2018
DOI: 10.1080/07853890.2018.1495337
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial thrombus resolution in non-valvular atrial fibrillation or flutter: biomarker substudy results from a prospective study with rivaroxaban (X-TRA)

Abstract: Biomarkers of inflammation are significantly associated with LA/LAA thrombus outcomes in AF patients prospectively treated with rivaroxaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…[22][23][24][25][26] The decrease of the mentioned biomarkers during rivaroxaban treatment has also been shown in a similar study in AF. 16 Here, von Willebrand's factor (vWF) and plasminogen activator inhibitor-1 were measured at baseline and after 6 weeks of treatment in addition to the biomarkers described here. The hs-CRP, D-dimer, vWF, and TAT showed a significant decrease in the mean levels from baseline to end of treatment with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26] The decrease of the mentioned biomarkers during rivaroxaban treatment has also been shown in a similar study in AF. 16 Here, von Willebrand's factor (vWF) and plasminogen activator inhibitor-1 were measured at baseline and after 6 weeks of treatment in addition to the biomarkers described here. The hs-CRP, D-dimer, vWF, and TAT showed a significant decrease in the mean levels from baseline to end of treatment with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…In the X-TRA biomarker substudy, high levels of inflammatory biomarkers in patients with AF who had left atrial/left atrial appendage thrombus were associated with the thrombus being completely resolved or reduced with rivaroxaban treatment and, therefore, also showed potential as predictive biomarkers. 16 These correlates require additional investigation to assess their clinical utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ammation has been con rmed to be associated with left atrial thrombosis in AF patients [20]. Previous studies have found that in ammatory biomarkers were signi cantly associated with left atrium or left atrial appendage thrombus outcomes in AF patients [21]. In conclusion, LDL-C/HDL-C may cause IS in NVAF patients by promoting atherosclerosis and left atrial or left atrial appendage thrombosis.…”
Section: Discussionmentioning
confidence: 79%
“…In ammation has been con rmed to be associated with left atrial thrombosis in AF patients [28]. Previous studies have found that in ammatory biomarkers are signi cantly associated with left atrium or left atrial appendage thrombus outcomes in AF patients [29]. In conclusion, LDL-C/HDL-C may cause IS in NVAF patients by promoting atherosclerosis and left atrial or left atrial appendage thrombosis.…”
Section: Discussionmentioning
confidence: 81%